Antecedents of Omnichannel purchase intention of apparel: A study among youth (International Journal of Environmental Sciences, 2025)
Understanding the dynamic relationship between different consumer behaviors is essential for brands to succeed in today's cutthroat business environment. The aim of the study was to examine various factors influencing customers’ purchase intention of various apparel brands using Omnichannel retailing among youth. Customer purchase intention has been found to be significantly influenced by personalized experiences, where customized interactions not only create a feeling of community but also have an impact on purchasing decisions. In this process, customer service is essential because timely, compassionate service increases customer loyalty and improves brand reputation. Customers' inclination to accept new goods or services is also greatly influenced by elements like social influence and individual inventiveness. Customers are more inclined to interact with new offerings if they perceive them to be more inventive. At the same time, social circles' advice and viewpoints frequently influence what people decide to buy. Another essential component of building lasting relationships is trust, since consumers are drawn to companies they believe to be trustworthy and open system for reward points.